Edukasi Kesehatan pada Kader Kesehatan Mengenai Stunting dan Pencegahannya Wilayah Kerja Puskesmas Benda Baru, Tangerang Selatan - Pratiwi, Rita Dwi; Andriati, Riris; Indah, Fenita Purnama Sari (Universitas Medan Area, 2026)
Stunting Incidence Over the Past Decade with 148.1 Million (22.3 Percent of Children Under 5 Years of Age Worldwide Affected) in 2022. Indonesia is included in the Third Country with the Highest Prevalence of Stunting Cases at 36.4%. The purpose of PkM is to provide health education related to stunting, its causes and prevention. In addition, it also introduced an information system related to stunting calculations. The community service activity was attended by all participants who attended a total of 53 health cadres of the Benda Baru Health Center. Activities still need to have more audience members so that the results are wider and more beneficial. The output of the implementation or solution as an indicator of the success of the program is to ask participants about the material explained during the PkM, namely the definition, causes, impacts, stunting prevention and also about calculations using stunting calculators. PkM is running smoothly. The results of the post-test score have increased compared to the pre-test score. This shows that there is an increase in public knowledge after counseling is carried out. The results of this community service are useful as a contribution of knowledge to Nursing and Public Health Promotion and Education Health Providing knowledge about stunting is expected to make children free from malnutrition and stunting.